Bruce Nauman, Contrapposto studies - Basualdo, Carlos 1964-; Basualdo, Carlos 1964-; Battle, Erica F.; Bourgeois, Caroline 1959- (Philadelphia Museum of Art, 2018)
"This publication marks the acquisition of Bruce Nauman's new, monumental work Contrapposto Studies, I through VII by the Philadelphia Museum of Art and the François Pinault Collection, Venice and Paris"...
Keywords: Nauman, Bruce -- 1941-; Nauman, Bruce -- 1941- -- Exhibitions; Philadelphia Museum of Art -- Exhibitions; Geschichte 1968-2016; Video installations (Art) -- United States -- Exhibitions; Video installations (Art) -- Pennsylvania -- Philadelphia -- Exhibitions; Video-Installation; Nauman, Bruce (1941-) / Contrapposto Studies